2012
DOI: 10.7861/clinmedicine.12-3-235
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of infliximab withdrawal after 12 months of treatment in patients with Crohn’s disease: how will NICE guidance affect patient care?

Abstract: ABSTRACT-Infliximab is a biological agent that is licensed for the treatment of severe Crohn's disease. The annual cost of infliximab treatment is approximately £16,456 (excl VAT). In May 2010, the National Institute for Health and Clinical Excellence (NICE) recommended that patients should receive biological agents as a planned course of treatment only until treatment failure or until 12 months after the start of treatment, whichever is shorter. Patients should then have their disease reassessed to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…If a patient is in clinical remission – as confirmed by clinical features, biological markers, or endoscopic or radiological studies – NICE recommends that treatment with biological agents be withdrawn, although the patient should continue to take either thiopurines or methotrexate. Of note, this conclusion was based on uncontrolled data from an abstract and a small retrospective case series …”
Section: What Are the Recommendations Of The Different Scientific Assmentioning
confidence: 99%
See 1 more Smart Citation
“…If a patient is in clinical remission – as confirmed by clinical features, biological markers, or endoscopic or radiological studies – NICE recommends that treatment with biological agents be withdrawn, although the patient should continue to take either thiopurines or methotrexate. Of note, this conclusion was based on uncontrolled data from an abstract and a small retrospective case series …”
Section: What Are the Recommendations Of The Different Scientific Assmentioning
confidence: 99%
“…Some authors have assessed the impact of the NICE guidelines on patient care by prospectively auditing patients who had been receiving IFX for 12 months or more . The audit provided the opportunity for full reassessment of disease and, for patients who were in clinical remission, the option to stop treatment.…”
Section: What Are the Recommendations Of The Different Scientific Assmentioning
confidence: 99%
“…Despite the reassuring data regarding successful retreatment in patients withdrawn from anti-TNF therapy, risk of relapse is often a contraindication to trial of withdrawal particularly for personal reasons such as work, education or a desire to become pregnant 11. It is perhaps, therefore, unsurprising that some patients have concerns regarding withdrawal of anti-TNF therapy 16 17…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a retrospective UK-wide study explored the outcome of anti-TNF withdrawal in inflammatory bowel disease and found that 35% of UC patients had relapsed within a year of cessation. [15] In addition, treatment withdrawal may not be the preferred option for many patients [16] or clinicians.…”
Section: The Futurementioning
confidence: 99%